Perilaku Masyarakat terhadap Kejadian DBD di Kecamatan Ciracas Jakarta Timur - Rojali Rojali; Awan Putri Amalia (Politeknik Kesehatan Kemenkes Mamuju, 2020)
Dengue Hemorrhagic Fever (DHF) is an infectious disease caused by the dengue virus and is transmitted by mosquitoes Aedes aegypti and Aedes albopictus. This study is an analytical study with a cross sectional approach with the title